Performance Evaluation of Composite Cross-Arm Structure under Different Magnitude of Loading - Mohamad D.; Beddu S.; Syamsir A.; Zahari N.M.; Abu Seman S.A.H.; Razali M.F.; Abas A.; Ng F.C. (IOP Publishing Ltd, 2023)
In this paper, the effects of load with increasing factor of safety on the mechanical performance and intra-laminar damage formation of cross-arm structure made up of two different schemes are studied. The composite structure has been numerically modelled by a finite element (FE) model. Research was carried out using a VUMAT subroutine to model intra-laminary damage formation in the analysed composite structure, and Hashin's failure criteria have been used. This investigation revealed that with a good combination of stacking sequence and ply properties as shown by scheme A which has combination of 90 and 45-degree plies at the both ends and much higher value of ply properties, a safety reserve can be obtained that provides a margin between actual load conditions and those leading to cross-arms structure failure. Published under licence by IOP Publishing Ltd.